Construction of the molecular structure model of the Shengli lignite using TG-GC/MS and FTIR spectrometry data. (1st September 2017) - Feng, Li; Zhao, Guangyao; Zhao, Yingya; Zhao, Maoshuang; Tang, Jiewu
Highlights: The construction method of molecular structure models of lignite was proposed. The structure model fragments were obtained via TG-GC/MS analysis. The structural parameters were obtained by peak-fitting of FTIR data. The model was optimized and revised on the basis of quantum chemistry. FTIR spectrum calculated based on the model is consistent with that of the sample. Abstract: The molecular structure model of the Shengli lignite was determined via TG-GC/MS for the analysis of the pyrolysis products' structure and contents, in combination with ultimate analysis and FTIR for the determination of its structure parameters. Then the model was constructed by hand referring to references, optimized and revised on the basis of quantum chemistry by semi-empirical and the second derivative force field. It was estimated that the cross-links were comprised of ether bond (O), aliphatic bond (CH2, CH2 CH2 ), ester bond, SS, etc., and heterocyclic compounds were mainly furan, indole, quinoline, etc., while its oxygen-containing functional groups were primarily carboxyl, hydroxyl, and ether. The molecular formula for the lignite structure model was C169 H140 O44 N3 S2 . A FTIR spectrum calculated based on the model is consistent with that of the experimental data.